2000
DOI: 10.1023/a:1026514032085
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Results suggest that pregnancy at an early age has a permanent beneficial association with density, while HRT has a transitory adverse association.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
24
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(27 citation statements)
references
References 50 publications
3
24
0
Order By: Relevance
“…A positive association between age at menarche and density was reported to be stronger in premenopausal women (El-Bastawissi et al , 2000; Vachon et al , 2000); in some studies (Vachon et al , 2000) these associations were attenuated in multivariate analyses. Hormone replacement therapy (HRT), older age at first child's birth, nulliparity, a family history of breast cancer, and alcohol consumption have been reported to be associated with increased breast density (Gram et al , 1995; El-Bastawissi et al , 2000; Vachon et al , 2000, 2002, 2005; Colacurci et al , 2001; Erel et al , 2001; Rutter et al , 2001; Gapstur et al , 2003; Ziv et al , 2003; Conner et al , 2004; Harvey et al , 2005; Boyd et al , 2006; Maskarinec et al , 2006; Titus-Ernstoff et al , 2006). Inconsistent relations with breast density have been reported for smoking, circulating hormone levels (blood estrogen, estrone levels, total estradiol levels, sex hormone-binding globulin), race/ethnicity, and a few polymorphisms in the estrogen metabolism pathway genes (Boyd et al , 2002; Haiman et al , 2002; Gapstur et al , 2003; Warwick et al , 2003; Conner et al , 2004; Aiello et al , 2005; Noh et al , 2006; Warren et al , 2006; Bremnes et al , 2007; Maskarinec et al , 2007; Tamimi et al , 2007; Verheus et al , 2007).…”
mentioning
confidence: 93%
See 2 more Smart Citations
“…A positive association between age at menarche and density was reported to be stronger in premenopausal women (El-Bastawissi et al , 2000; Vachon et al , 2000); in some studies (Vachon et al , 2000) these associations were attenuated in multivariate analyses. Hormone replacement therapy (HRT), older age at first child's birth, nulliparity, a family history of breast cancer, and alcohol consumption have been reported to be associated with increased breast density (Gram et al , 1995; El-Bastawissi et al , 2000; Vachon et al , 2000, 2002, 2005; Colacurci et al , 2001; Erel et al , 2001; Rutter et al , 2001; Gapstur et al , 2003; Ziv et al , 2003; Conner et al , 2004; Harvey et al , 2005; Boyd et al , 2006; Maskarinec et al , 2006; Titus-Ernstoff et al , 2006). Inconsistent relations with breast density have been reported for smoking, circulating hormone levels (blood estrogen, estrone levels, total estradiol levels, sex hormone-binding globulin), race/ethnicity, and a few polymorphisms in the estrogen metabolism pathway genes (Boyd et al , 2002; Haiman et al , 2002; Gapstur et al , 2003; Warwick et al , 2003; Conner et al , 2004; Aiello et al , 2005; Noh et al , 2006; Warren et al , 2006; Bremnes et al , 2007; Maskarinec et al , 2007; Tamimi et al , 2007; Verheus et al , 2007).…”
mentioning
confidence: 93%
“…Inverse associations with breast density were reported for older age, parity, postmenopausal status, and high body mass index (BMI) (El-Bastawissi et al , 2000; Lam et al , 2000; Vachon et al , 2000; Colacurci et al , 2001; Erel et al , 2001; Vachon et al , 2002; Gapstur et al , 2003; Warwick et al , 2003; Conner et al , 2004; Vachon et al , 2005; Maskarinec et al , 2006; Modugno et al , 2006; Titus-Ernstoff et al , 2006; Ginsburg et al , 2008; Johansson et al , 2008; Kelemen et al , 2008). A positive association between age at menarche and density was reported to be stronger in premenopausal women (El-Bastawissi et al , 2000; Vachon et al , 2000); in some studies (Vachon et al , 2000) these associations were attenuated in multivariate analyses.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While research has consistently shown a negative association between increasing parity and breast density (e.g., [10, 11]), findings have been less consistent for an association between breast density and older age at first birth (as reviewed in [12]). A few studies have demonstrated that some of the same birth characteristics shown to be associated with increased breast cancer risk were associated with high breast density, specifically, preterm birth, nulliparity/low parity, older age at first birth, and high birth weight [10, 11, 13, 14]. Lope et al [14] found that duration of breastfeeding was positively associated with breast density, while Butler et al [10] found no significant association between breast-feeding and breast density.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, it has been reported that age at first birth, family history of BC, mammographic density or genetic factors are also associated with greater risk [4,5]. Having a reliable individual BC risk estimate based on known factors makes it possible to develop personalized screening programs and optimize the use of resources in a population.…”
Section: Introductionmentioning
confidence: 99%